2001
DOI: 10.1111/j.1749-6632.2001.tb05828.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms in Chemical Intolerance and Related Conditions

Abstract: The symptom of chemical intolerance may occur in isolation, but often occurs in conjunction with other chronic symptoms such as pain, fatigue, memory disturbances, etc. This frequent clustering of symptoms in individuals has led to the definition of several chronic multisymptom syndromes, such as multiple chemical sensitivity, fibromyalgia, chronic fatigue syndrome, and Gulf War illnesses. The aggregate research into these syndromes has suggested some unifying mechanisms that contribute to symptomatology. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 106 publications
(189 reference statements)
0
13
0
3
Order By: Relevance
“…Aggregated research concerning the pathophysiology of CMI has suggested that an aberrant function of centrally mediated processes may play a significant role in initiating and/or perpetuating symptoms [13]. In line with these findings, a growing body of literature reports imbalances in nervous system functions in patients with perceived electrical hypersensitivity [14][15][16].…”
Section: Introductionmentioning
confidence: 96%
“…Aggregated research concerning the pathophysiology of CMI has suggested that an aberrant function of centrally mediated processes may play a significant role in initiating and/or perpetuating symptoms [13]. In line with these findings, a growing body of literature reports imbalances in nervous system functions in patients with perceived electrical hypersensitivity [14][15][16].…”
Section: Introductionmentioning
confidence: 96%
“…In most of these patients, where low cortisol levels were found, there were also histories of poor coping abilities, multiple major stressful life events, and in women with chronic pelvic pain, high rates of physical and sexual abuse. In fact it would appear that most individuals with serious multiple unexplicable health complaints have previously suffered from clusters of severe infectious complications, physical or emotional trauma [69] -factors earlier in this paper seen to have the ability to predispose to hypofunction of the CRH/HPA-axis and to stimulate the production of pro-inflammatory cytokines. Preliminary indications are that adrenal insufficiency and an above normal sensitivity to the negative feedback may underlie the hypofunction of the HPA-axis [59].…”
Section: Sickness Behavior and Disorders Associated By Low Cortisolmentioning
confidence: 72%
“…Controversy still exists as to whether syndromes consisting of subjective health complaints represent several or variations on one general condition. In fact, it has been suggested that most of the multisymptom syndromes like somatoform disorders, fibromyalgia, chronic fatigue syndrome and exposure syndromes such as Gulf War illnesses, sick-building syndrome, illnesses found in women with silicon breast implants, multiple chemical sensitivity and others are related in terms of their stressexposure histories, their psychological profiles, and some neurological alterations [69]. No distinction will therefore be made for the purpose of this discussion.…”
Section: Sickness Behavior and Disorders Associated By Low Cortisolmentioning
confidence: 99%
See 1 more Smart Citation
“…24 These terms have common core features. Each of them refers to subjective experiences obviously real to those who undergo them, often to the point of debility; on the other hand, researchers have striven to substantiate the biomedical substrate of such experiences but so far have largely come up empty-handed.…”
Section: Methodsmentioning
confidence: 99%